Recurrent Kawasaki Disease: A Case Report of Three Separate Episodes at >4-Year Intervals - Nikita Goswami; Katherine Marzan; Elizabeth De Oliveira; Sharon Wagner-Lees; Jacqueline Szmuszkovicz (MDPI AG, 2018)
Kawasaki disease (KD) is a self-limited systemic vasculitis, most often occurring in children 1⁻5 years old. It has a 2% recurrence rate and is associated with coronary aneurysms (CA), which can develop within two weeks of onset. A 25% increased risk is noted in patients who are recalcitrant to treatment. We describe a patient with recurrence of KD three times, approximately four years apart. A 10-year-old female with two previous episodes of KD, at 11 months and five years of age), in which she met five out of five criteria for KD and had no coronary involvement, presented with 15 days of fever, conjunctivitis and mucocutaneous changes. Infectious work-up was negative, and she was diagnosed with incomplete KD meeting three out of five criteria. An echocardiogram (ECHO) on day 12 revealed dilation of the right coronary artery (RCA) and left coronary artery (LCA). Treatment with intravenous immunoglobulin (IVIG) and high-dose aspirin was started at an outside hospital. After transfer, serial ECHOs showed evolving coronary aneurysms, left anterior descending (LAD) z-score + 8.2 and RCA z-score + 4.0. She received 10 mg/kg infliximab (day 18) and began clopidogrel. A cardiac MRI (day 20) demonstrated progression of the LAD aneurysm, with a z-score + 13, and warfarin was started. To our knowledge, this is the first report of recurrent KD occurring three times at ~5 year intervals.